Phenantridine alkaloids from Zanthoxylum myriacanthum - Sukari, M.A; Salim, W.S.W; Ibrahim, N.H; Rahmani, M; Aimi, N; Kitajima, M (Elsevier BV, 1999)
Plant. Zanthoxylum myriacanthum Wall. (Rutaceae), air dried stem barks collected from Air Keroh, Melaka (Malaysia) in 1994 and identified by Prof. Ruth Kiew, Universiti Putra Malaysia. A voucher specimen has been deposited in the Herbarium of the Department of Biology, Universiti Putra Malaysia.